Volume Of My Heart.

Level pending

In the half heart curve x 2 + ( 5 y 4 x ) 2 = 1 x^2 + (\dfrac{5y}{4} - \sqrt{x})^2 = 1 above, A B \overline{\rm AB} goes from the positive y y intercept to the positive x x intercept and points A , B , D A,B,D encloses the region R R .

If the region R R of the half heart curve x 2 + ( 5 y 4 x ) 2 = 1 x^2 + (\dfrac{5y}{4} - \sqrt{x})^2 = 1 is revolved about the y axis the resulting volume is V R = a 3 π b ( 1 c 1 c ( ϕ 1 ) c a + 1 a c ( ϕ 1 ) a a b ( ϕ 1 ) b a ) V_{R} = \dfrac{a^3\pi}{b}(\dfrac{1}{c} - \dfrac{1}{c}(\phi - 1)^{\frac{c}{a}} + \frac{1}{a * c}(\phi - 1)^{a} -\dfrac{a}{b}(\phi - 1)^{\frac{b}{a}}) .

Find a + b + c a + b + c , where a , b a,b and c c are coprime positive integers and ϕ \phi is the golden ratio.


The answer is 10.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Dec 14, 2019

For the x x intercept of y 1 = 4 5 ( x 1 x 2 ) y_{1} = \dfrac{4}{5} (\sqrt{x} - \sqrt{1 - x^2}) we obtain:

x 2 + x 1 = 0 x = 1 ± 5 2 x^2 + x - 1 = 0 \implies x = \dfrac{-1 \pm \sqrt{5}}{2} , since x = 1 + 5 2 = ϕ x = -\dfrac{1 + \sqrt{5}}{2} = -\phi results in a complex valued square root x = 5 1 2 \implies x = \dfrac{\sqrt{5} - 1}{2} is the x intercept of y 1 = 4 5 ( x 1 x 2 ) y_{1} = \dfrac{4}{5} (\sqrt{x} - \sqrt{1 - x^2}) .

The equation of the line passing thru A : ( 0 , 4 5 ) A: (0,\dfrac{4}{5}) and B : ( 5 1 2 , 0 ) B: (\dfrac{\sqrt{5} - 1}{2},0) is:

y = 4 5 ( 2 x 5 1 + 1 ) y = \dfrac{4}{5} (\dfrac{-2x}{\sqrt{5} - 1} + 1) \implies

Let ϕ = 5 + 1 2 \phi = \dfrac{\sqrt{5} + 1}{2}

\implies

V R = 2 π ( 4 5 ) 0 ϕ 1 V_{R} = 2\pi (\dfrac{4}{5}) \int_{0}^{\phi - 1} x ( 1 x ϕ 1 + 1 x 2 x ) d x x(1 - \dfrac{x}{\phi - 1} + \sqrt{1 - x^2} - \sqrt{x}) dx

= 8 π 5 0 ϕ 1 ( x x 2 ϕ 1 + x ( 1 x 2 ) 1 2 x 3 2 ) d x = \dfrac{8\pi}{5} \int_{0}^{\phi - 1} (x - \dfrac{x^2}{\phi - 1} + x(1 - x^2)^{\frac{1}{2}} - x^{\frac{3}{2}}) dx

= 8 π 5 ( x 2 2 x 3 3 ( ϕ 1 ) 1 3 ( 1 x 2 ) 3 2 2 5 x 5 2 ) 0 ϕ 1 = \dfrac{8\pi}{5} (\dfrac{x^2}{2} - \dfrac{x^3}{3(\phi - 1)} - \dfrac{1}{3}(1 - x^2)^{\frac{3}{2}} - \dfrac{2}{5}x^{\frac{5}{2}})|_{0}^{\phi - 1}

= 8 π 5 ( ( ϕ 1 ) 2 6 + 1 3 1 3 ( 1 ( ϕ 1 ) 2 ) 3 2 2 5 ( ϕ 1 ) 5 2 ) = \dfrac{8\pi}{5}(\dfrac{(\phi - 1)^2}{6} + \dfrac{1}{3} - \dfrac{1}{3}(1 - (\phi - 1)^2)^\frac{3}{2} - \dfrac{2}{5}(\phi - 1)^{\frac{5}{2}})

= 8 π 5 ( 1 3 1 3 ( ϕ 1 ) 3 2 + 1 6 ( ϕ 1 ) 2 2 5 ( ϕ 1 ) 5 2 ) = \dfrac{8\pi}{5}(\dfrac{1}{3} - \dfrac{1}{3}(\phi - 1)^{\frac{3}{2}} + \dfrac{1}{6}(\phi - 1)^2 - \dfrac{2}{5}(\phi - 1)^{\frac{5}{2}})

= 2 3 π 5 ( 1 3 1 3 ( ϕ 1 ) 3 2 + 1 2 3 ( ϕ 1 ) 2 2 5 ( ϕ 1 ) 5 2 ) = = \dfrac{2^3\pi}{5}(\dfrac{1}{3} - \dfrac{1}{3}(\phi - 1)^{\frac{3}{2}} + \frac{1}{2 * 3}(\phi - 1)^2 - \dfrac{2}{5}(\phi - 1)^{\frac{5}{2}}) =

= a 3 π b ( 1 c 1 c ( ϕ 1 ) c a + 1 a c ( ϕ 1 ) a a b ( ϕ 1 ) b a ) = \dfrac{a^3\pi}{b}(\dfrac{1}{c} - \dfrac{1}{c}(\phi - 1)^{\frac{c}{a}} + \frac{1}{a * c}(\phi - 1)^{a} -\dfrac{a}{b}(\phi - 1)^{\frac{b}{a}})

a + b + c = 10 \implies a + b + c = \boxed{10} .

Note: 1 ( ϕ 1 ) 2 = 2 ϕ ϕ 2 = 5 + 1 5 + 2 5 + 1 4 = 2 5 2 4 = 1 - (\phi - 1)^2 = 2\phi - \phi^2 = \sqrt{5} + 1 - \dfrac{5 + 2\sqrt{5} + 1}{4} = \dfrac{2\sqrt{5} - 2}{4} = 5 1 2 = ϕ 1 \dfrac{\sqrt{5} - 1}{2} = \phi - 1 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...